The iconicity of picture communication symbols for rural Zulu children - Lize Haupt (South African Journal of Communication Disorders, 2002)
The purpose of this study was to investigate the iconicity of selected Picture Communication Symbols (PCS) for rural Zulu ten-year-olds. Participants were presented with copies of a commercially available communication overlay without glosses. They were required to match a symbol with each of 36 spoken Zulu labels. With both strict and lenient scoring criteria applied, and 11.1% (respectively) of the symbols on the communication overlay emerged as iconic for participants. It was further established that the position of symbols on the overlay, the total frequency of selection of symbols, and gender did not influence results. An analysis of errors revealed that for some symbols many of the participants agreed on a single specific label, be it the target label or a non-target label; while for other symbols there were either many possible labels, or none. The term distinctiveness was coined to describe how well defined or specific were the evoked meanings triggered by a symbol in the viewers' minds. Results suggest that participants did not make maximum use of the information provided by arrows in the symbols. This finding could be ascribed to the opaqueness of arrows and participants' lack of previous experience with these conventional cues in pictures, as well as the traditional oral nature of the Zulu culture.